Planar waveguides based on nanocrystalline and Er3+ doped SnO2 - Goncalves, R. R.; Ferrari, M.; Chiasera, A.; Montagna, M.; Morais, E. A.; Scalvi, LVA; Santilli, Celso Valentim [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, SJL (Trans Tech Publications Ltd, 2002)
Luminescent SnO2: x%mol Er3+ (x=0.1-2.0) thin films have been spin coated on borosilicate and silica substrates from water colloidal suspensions that could be prepared containing up to 40% in weight SnO2 nanocrystalline powders. High Resolution Transmission Electron Microscopy results show the well known SnO2 cassiterite structure and nanocrystallites around 10 nm in diameter, corroborating results from X-ray diffraction. Mono and multi layers have been prepared from the stable colloidal suspensions and films thickness was observed to increase linearly, up to 200 nm, with the colloidal suspensions nanoparticles amount. Excitation and emission spectra have been measured and Er3+ ions were found to be essentially incorporated into the cassiterite structure, substituting for Sn4+, for doping concentration lower than 0.05 mol%. Er3+ ions also appear segregated at the grains surface for higher doping concentration. The optical parameters (refractive index, thickness and propagating modes) of a waveguide sample were measured at 632.8 and 543.4 nm by the prism coupling technique. A monomodal waveguide was obtained with attenuation loss of 3.5 dB/cm along a 2.5 cm optical path.
Keywords: planar waveguides; tin oxide; erbium